2016
DOI: 10.1111/jpm.12276
|View full text |Cite
|
Sign up to set email alerts
|

Nurses experiences of working in Crisis Resolution Home Treatment Teams with its additional gatekeeping responsibilities

Abstract: It is evident through nurse's experiences of working within CRHTT and gatekeeping that their roles were very dynamic and challenging. A positive risk-taking approach contributed towards the success of CRHTT as gatekeepers. Family members played a significant role in ensuring gatekeeping remained a priority consistent with Government targets. Clinical Implications and recommendations for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 18 publications
1
14
0
3
Order By: Relevance
“…This is in line with the findings from previous research, which had already highlighted the importance of family, as having a central role in recovery. Its involvement is seen as a valuable and qualified resource, responsible for assisting with the care provision (41). Importantly, the way in which a family starts a compulsory admission process has an effect on how individuals consider the first days of admission and is decisive in the patient's whole experience (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the findings from previous research, which had already highlighted the importance of family, as having a central role in recovery. Its involvement is seen as a valuable and qualified resource, responsible for assisting with the care provision (41). Importantly, the way in which a family starts a compulsory admission process has an effect on how individuals consider the first days of admission and is decisive in the patient's whole experience (42).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the way in which a family starts a compulsory admission process has an effect on how individuals consider the first days of admission and is decisive in the patient's whole experience (42). It has been emphasized already that working in partnership and having discussions between the staff and the family members contributes to the development of best practice (43), to deliver safe and effective interventions (41). Despite the importance of family in mental health care, some families in London reported that they are treated as an irrelevant and troublesome part by the British mental health system (44).…”
Section: Discussionmentioning
confidence: 99%
“…One strategy commonly suggested to improve integration between community and hospital based services is the assessment of all patients potentially requiring an inpatient admission by a central acute community team (Begum & Riordan, 2016;Chisholm & Ford, 2004;Hasselberg et al, 2011;Murphy et al, 2012;National Institute for Mental Health, 2006).…”
Section: Towards the Development And Delivery Of Integrated Service Modelsmentioning
confidence: 99%
“…This team is often the first point of call for family members when seeking help for their relatives. The team has a gatekeeping role for access to mental health services (Begum & Riordan, ). It has been reported that best practice involves partnership between crisis team, consumers and their carers during the delivery of care (Karlsson, Borg, Eklund, & Kim, ; Ness, Karlsson, Borg, Biong, & Hesook, ).…”
Section: Introductionmentioning
confidence: 99%